Bi-Lingual teaching and learning: Effectiveness and challenges in postgraduate studies - Lee Kar Ling (Laureate Education Inc, 2013)
The purpose of this study was to assess the effectiveness of the use of bilingual teaching and learning methodology for Vietnamese postgraduate students from 2011-2012. Overall, the findings indicated relatively positive outcomes in most of the spectrum evaluated or assessed. These findings were then compared with previous researches and to ascertain the applicability to fundamental theories underpinning bilingual education to determine the correlation between theory and practice. This research provided an in-depth contextual based research that contributed to an extensive understanding of the effectiveness of the adoption of bilingual teaching and learning at postgraduate level within ASEAN countries. The research will also provide a platform for development nations to gain accesses to the required knowledge, skills, capabilities, and competencies that have thus far eluded them due to language barrier, thereby providing these nations with the impetus to grow and develop further as a nation via the effective development of the country's human capital.  DOI: 10.18870/hlrc.v3i4.167